A multi-aspect coordination HDRED site selection framework under multi-type heterogeneous environments. (June 2021) - Zhao, Chengwei; Xu, Xuanhua; Liu, Ruihuan; He, Jishan
Abstract: Site selection is a critical link in hot dry rock exploration and development (HDRED). However, some problems such as incoordination of the qualitative and quantitative criteria, inaccurate information descriptions, information loss or distortion, incomplete consideration of the coordinating influence of the subjective-objective aspects, and criteria's complex interactions exist in the extant site selection methods. To overcome those deficiencies, an innovative multi-aspect coordination framework under heterogeneous environments is proposed to select the optimal HDRED site. First, a comprehensive HDRED site selection criteria system is established from the perspective of sustainability. Second, multi-type heterogeneous information of crisp numbers, interval numbers, triangular intuitionistic fuzzy numbers, and interval-valued intuitionistic uncertain linguistic variables is adopted to accurately describe criteria, which not only can achieve varied criteria coordination, but improves the collection and processing of criteria information. Third, the heterogeneous entropy-DEMATEL model is proposed to more reasonably determine weights. Next, the heterogeneous TOPSIS is constructed to rank alternatives while avoiding information distortion or loss. Finally, a case from China is considered for comparative analysis and sensitivity analysis. The results indicate that the proposed framework can effectively promote the large-scale development of hot dry rock and has strong practical and popularizing value. Highlights: A multi-aspect coordination HDRED siting framework is proposed. A comprehensive criteria system for HDRED site selection is built. Criteria information can be accurately described and handled in proposed framework. Heterogeneous entropy-DEMATEL method is built to more reasonably determine weight. Heterogeneous TOPSIS model ranks the alternatives without information loss.